Transcriptomic Comparison of Liver Tissue across Different Largemouth Bass (Micropterus salmoides) Strains - Fan Zhou; Xuelin Zhang; Gaohua Yao; Xiaoming Chen; Ming Qi; Qin Zhou; Ningyu Zhu; Qinghui Meng; Yu Zhang; Xueyan Ding (Fishes, 2023)
Over the past few years, China has become a hotspot for the domestication of the commercially valuable largemouth bass (Micropterus salmoides). Although the food preference of this fish has been studied, little is known about the genes regulating its growth. Population breeding was performed using two indigenous strains (QT1 and QT2), with the results showing that the organ/body ratio, abdominal fat rate and the body weight gain of QT1 and QT2 were higher than for the offspring YL1 and Y3 which are extensively cultured in China. Subsequent RNA sequencing (RNA-Seq) allowed for the identification of potential genes and pathways involved in growth performance. Overall, the transcriptome analysis generated 89,056 transcripts and 42,529 Unigenes. A PCA revealed significant differences between QT1 and the other three strains, while the other three strains did not show much difference. A KEGG enrichment analysis of differentially expressed genes showed that steroid biosynthesis was the most enriched pathway among the four strains. These pathways could be related to the growth of largemouth bass. In addition, a co-expression network analysis suggested a strong interaction between liver steroid biosynthesis and the genes for photosynthesis, secondary metabolism and stress response. Taken together, the above results can provide new insights into the liver metabolism of different strains of largemouth bass during culture and provide references for the subsequent domestication and breeding programs of largemouth bass.